Coronary artery involvement in type A aortic dissection: Fate of the coronaries. Issue 12 (30th September 2022) - Kayali, Fatima; Jubouri, Matti; Al‐Tawil, Mohammed; Tan, Sven Z. C. P.; Williams, Ian M.; Mohammed, Idhrees; Velayudhan, Bashi; Bashir, Mohamad
Abstract: Background: Type A aortic dissection (TAAD) involves a tear in the intimal layer of the thoracic aorta proximal to the left subclavian artery, and hence, carries a high risk of mortality and morbidity and requires urgent intervention. This dissection can extend into the main coronary arteries. Coronary artery involvement in TAAD can either be due to retrograde extension of the dissection flap into the coronaries or compression and/or blockage of these vessels by the dissection flap, possibly causing myocardial ischemia. Due to the emergent nature of TAAD, coronary involvement is often missed during diagnosis, thereby delaying the required intervention. Aims: The main scope of this review is to summarize the literature on the incidence, mechanism, diagnosis, and treatment of coronary artery involvement in TAAD. Methods: A comprehensive literature search was performed using multiple electronic databases, including PubMed, Ovid, Scopus and Embase, to identify and extract relevant studies. Results: Incidence of coronary artery involvement in TAAD was seldom reported in the literature, however, some studies have described patients diagnosed either preoperatively, intraoperatively following aortic clamping, or even during autopsy. Among the few studies that reported on this matter, the treatment choice for coronary involvement in TAAD was varied, with the majority revascularizing the coronary arteries using coronary artery bypass grafting or direct local repair of the vessels. It is well‐established that coronary artery involvement in TAAD adds to the already high mortality and morbidity associated with this disease. Lastly, the right main coronary artery was often more implicated than the left. Conclusion: This review reiterates the significance of an accurate diagnosis and timely and effective interventions to improve prognosis. Finally, further large cohort studies and longer trials are needed to reach a definitive consensus on the best approach for coronary involvement in TAAD.